2010
DOI: 10.1016/j.neuroimage.2010.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of brain aging in middle-aged and older adults: Regional and individual differences

Abstract: The human brain changes with age. However, the rate and the trajectories of change vary among the brain regions and among individuals, and the reasons for these differences are unclear. In a sample of healthy middle-aged and older adults, we examined mean volume change and individual differences in the rate of change in 12 regional brain volumes over approximately 30 months. In addition to the baseline assessment, there were two follow-ups, 15 months apart. We observed significant average shrinkage of the hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
444
11
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 549 publications
(504 citation statements)
references
References 51 publications
47
444
11
2
Order By: Relevance
“…Another study found a similar aging pattern that was observed over a 5-year period (Raz et al 2005). Moreover, WM loss in the prefrontal area of healthy old individuals was found to occur after only 30 months (Raz et al 2010), suggesting enhanced regional sensitivity to aging. The Baltimore Longitudinal Study reported age-related changes in MRIderived signal intensity, which was believed to reflect demyelination and changes in water, protein, and mineral content in the old (Davatzikos and Resnick 2002).…”
Section: Longitudinal Imaging Studies In Humanssupporting
confidence: 63%
“…Another study found a similar aging pattern that was observed over a 5-year period (Raz et al 2005). Moreover, WM loss in the prefrontal area of healthy old individuals was found to occur after only 30 months (Raz et al 2010), suggesting enhanced regional sensitivity to aging. The Baltimore Longitudinal Study reported age-related changes in MRIderived signal intensity, which was believed to reflect demyelination and changes in water, protein, and mineral content in the old (Davatzikos and Resnick 2002).…”
Section: Longitudinal Imaging Studies In Humanssupporting
confidence: 63%
“…Age is an additional factor that leads to brain tissue volume decline in humans (Pfefferbaum et al, 1994;Pfefferbaum et al, 2013;Raz et al, 2010;Raz et al, 2005). The animals studied here ranged in age from 5.5 to 9.6 years at the beginning of the induction period, with a mean ± SD of 7.2 ± 1.6 years.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the propensity to confidently endorse novel events as experienced before is likely to reflect failures in executive and control functions implemented by frontal regions (Gilboa et al, 2006). In ageing, these brain regions are among the areas that undergo the strongest changes (Raz, Ghisletta, Rodrigue, Kennedy, & Lindenberger, 2010;Raz et al, 2005). Thus age-related increases in the propensity to false recognition with high subjective confidence may be related to deficits in the ability to carry out executive and monitoring operations confined to the PFC (Jacoby & Rhodes, 2006;Schacter et al, 1997).…”
Section: Mechanisms Of False Memory In Ageingmentioning
confidence: 99%